RECTAL FOREIGN BODY CASE REPORTS AND REVIEW OF LITERATURE IN SULAYMANIYAH- TEACHING HOSPITAL - Qaradaxy, Seerwan Hama Shareef; Faraj, Shvan Jamal Hassan (Journal of Sulaimani Medical College, 2024)
Background Rectal foreign bodies present the surgeon with a diffi cult management dilemma, as the type of object, host anatomy, time from insertion, associated injuries, and amount of local contamination may vary widely. Reluctance to seek medical help and to provide details about the incident often makes diagnosis diffi cult. Management of these patients may be challenging, as presentation is usually delayed after multiple attempts at removal by the patients themselves have proven unsuccessful. Objective The primary aim of our study is to identify patients diagnosed with rectal foreign bodies in Sulaymaniyah Teaching Hospital in Sulaymaniyah governorate/ Iraq over three years. All underwent surgical management and follow-up. Patients and Methods Five patients with rectal foreign bodies are reported in this paper, all of them are male. Their ages range from 45-65 years, and the mean age is 55. Over three years, they were hospitalized and treated at Sulaymaniyah Teaching Hospital. Following a thorough history, physical examination, and imaging, the patients underwent surgery. In addition to direct questioning the patients to obtain their consent, information was gathered from the medical records of Sulaymaniyah Teaching Hospital. Results Complete retrieval of the foreign bodies by surgical approach was reported in fi ve patients included in the study, under general anesthesia two of the cases underwent laparotomy while the other three had extraction. An uneventful post-operative period in all of them. No mortality was reported in any of the patients. Conclusion Rectal foreign body cases are rare and require precise diagnosis by physical examination and imaging modalities. The primary management method in our study was surgical removal and follow-up.
Keywords: Rectal foreign body; Extraction; and Laparotomy